Relationship between salt intake as estimated by a brief self-administered diet-history questionnaire (BDHQ) and 24-h urinary salt excretion in hypertensive patients - Sakata, Satoko; Tsuchihashi, Takuya; Oniki, Hideyuki; Tominaga, Mitsuhiro; Arakawa, Kimika; Sakaki, Minako; Kitazono, Takanari (Hypertension research, 2015)
Assessing an individual's salt intake is necessary for providing guidance with respect to salt restriction. However, the methods that exist for assessing salt intake have both merits and limitations. Therefore, the evaluation methods should be selected for their appropriateness to the patients and the environment of the medical facilities. The purpose of the present study was to investigate the validity of a brief self-administered diet-history questionnaire (BDHQ) by comparing the responses with 24-h urinary salt excretion. A total of 136 hypertensive outpatients (54 men and 82 women) were included in this study. All subjects were given the BDHQ and performed 24-h home urine collection. The energy-adjusted salt intake as assessed by the BDHQ was 12.3 (95% confidence interval: 11.8-12.9) g per day, and the urinary salt excretion evaluated by 24-h urinary collection was 9.0 (8.4-9.5) g per day. The energy-adjusted salt intake assessed by the BDHQ correlated significantly with the urinary salt excretion evaluated by 24-h urinary collection (r=0.34, P<0.001). In conclusion, the estimated salt intake evaluated by the BDHQ weakly, but significantly, correlated with 24-h urinary salt excretion. In clinical practice, it seems important to utilize both methods to assess an individual's salt intake in order to provide adequate guidance for salt restriction.